Laser assisted glass frit sealing of dye-sensitized solar cells - Fernando Ribeiro (2012)
A new effective sealing method was developed for application in dye-sensitized solar cells. The sealing method employs a cord of a low temperature fusing glass frit paste that bounds the entire perimeter of the substrate. The glass precursor was heated to its melting point assisted by a laser beam, allowing the two substrates of the cell to be completely sealed. In the present work, the feasibility of this laser assisted glass paste sealing process is investigated and the best laser operating conditions are determined. Different tests were performed to the sealed samples at optimized sealing conditions and conclusions drawn. The glass-sealed samples were compared with results from conventional sealing based on commercial thermoplastics sealants. The results obtained from leakage, temperature and strength tests showed that the glass-sealing technique is better than the conventional method.